Acoustic Wave Propagation in a Trifurcated Lined Waveguide. (20th June 2011) - Ayub, M.; Tiwana, M. H.; Mann, A. B.; Zaman, H.
Abstract : The diffraction of sound from a semi-infinite soft duct is investigated. The soft duct is symmetrically located inside an acoustically lined but infinite duct. A closed-form solution is obtained using integral transform and Jones' method based on Wiener-Hopf technique. The graphical results are presented, which show how effectively the unwanted noise can be reduced by proper selection of different parameters. The kernel functions are factorized with different approaches. The results may be used to design acoustic barriers and noise reduction devices.